Analogical Rationality in Social Sciences - Rengifo-Castañeda, Carlos-Adolfo (European Journal of Social Science Education and Research, 2019)
This research article proposes a conception of analogical rationality, which operates in the social sciences as well as in the natural sciences, according to "epistemic, ontological and pragmatic" conditions. According to this, in this paper it is intended: First, to account for analogical rationality according to epistemic, ontological and pragmatic conditions, contrasting with this, the classical conception of rationality. And second, on the basis of the above, to enable by analogical rationality a status of scientificity for the social sciences by justifying rational beliefs and decisions, according to this tripartite condition